A bibliometric analysis of international publication trends in brain atrophy research (2008–2023) - Wang, Juwei; Chen, Tingting; Xie, Jiayi; Zhao, Sheng; Jiang, Yue; Zhang, Huihe; Zhu, Wenzong (Frontiers in Neurology, 2024)
Background: Brain atrophy is a type of neurological and psychiatric disorder characterized by a decrease in brain tissue volume and weight for various reasons and can have a serious impact on the quality of life of patients. Although there are many studies on brain atrophy, there is a lack of relevant bibliometric studies.Therefore, this study aims to provide a visual analysis of global trends in midbrain atrophy research over the past 16 years.Methods: CiteSpace and VOSviewer were used to visually analyse publication output, scientific collaborations, cocitations, publishing journals, and keywords to determine the current status and future trends of brain atrophy research. Materials published from 2008 to 2023 were collected from the Web of Science Core Collection (WoSCC) database. This study placed no restrictions on the types of literature and focused on English language publications.Results: A total of 3371 publications were included in the analysis. From 2008 to 2023, the number of publications increased annually. In terms of national and academic institutions, universities in the United States and University College London rank first in publication out. Barkhof Frederik and Zivadinov Robert are the most prolific researchers in this field. The publication with the highest cocitation strength is "Deep gray matter volume loss drives disability worsening in multiple clerosissclerosis". Keyword clustering analysis showed that "Alzheimer's disease" and "multiple sclerosis" are current popular topics. The analysis of emergent words indicates that "cerebral small vessel disease", "neurogenerationneurodegeneration", and "cortex/grey matter volume" may become hot research topics in the coming years.This study analyses papers on brain atrophy from the past 16 years, providing a new perspective for research in this field. In the past 16 years, research on brain atrophy has received increasing attention. The quality of articles in this field is generally high. Extensive national cooperation already exists.The statistical results indicate that a stable core author group in the field of brain atrophy has almost formed.